Multi-objective optimal design of a toroidally wound radial-flux halbach permanent magnet array limited angle torque motor - Luk, Patrick Chi-Kwong; Wu, Shuai (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents the modeling, optimization and validation of a toroidally wound radial-flux Halbach array permanent magnet limited angle torque motor. A fully parameterized and flexible equivalent magnetic circuit model of the proposed motor, which is arranged in matrix form by means of Kirchhoff’s current laws for computational efficiency and ease of extension, is introduced for preliminary design. To optimize the design, a multi-objective optimization process is carried out and the multi-objective particle swarm optimization method is used to obtain the Pareto front of the desired objectives. An approved solution in Pareto front is selected and validated by finite element analysis method. A prototype based on the final design is built and tested. The experiment results further underpin the effectiveness of the proposed design and optimization approach.
Keywords: Brushless motor; direct current motors; finite-element analysis (FEA); Halbach array; limited angle torque motor (LATM); magnetic circuit; multiobjective optimization (MOO); Pareto optimization